ANALISIS KOMUNIKASI INOVASI PELAKSANAAN LAYANAN ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) DALAM MENINGKATKAN KETERTIBAN LALU LINTAS DI KOTA SAMARINDA - Nurhaan, Nurasimah (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2024)
Research on the Application of Communication Innovations in the Implementation of Electronic Traffic Law Enforcement (ETLE) Services to Improve Traffic Order in Samarinda City has the aim of knowing how the form of application of innovation communication used by the Samarinda Police in conducting socialization related to ETLE to the public using descriptive qualitative research methods that refer to the theory of diffusion of innovation from Everett Rogers. The subject of this research is ETLE with data collection techniques are interviews as primary data and documentation results as secondary data. This study reviews the application of innovation communication in the implementation of Electronic Traffic Law Enforcement (ETLE) services to improve traffic discipline in Samarinda City. This research approach focuses on the stages of decision-making detailed in the Diffusion of Innovation theory, namely Knowledge, Persuasion, Implementation, and Confirmation, without including the decision stage. At the knowledge stage, this research focuses on discussing the awareness of the Samarinda Police as the recipient of innovations related to ETLE. The persuasion stage discusses the use of communication used by the Samarinda Police to socialize ETLE to the population. Implementation is the stage where Samarinda Police implements ETLE innovations in Samarinda City. The confirmation stage is the final step which includes strengthening the Polresta's decision to implement ETLE innovation communication, which involves community responses to the application of ETLE innovation communication in Samarinda City by the Samarinda Police. The main result of this research is the way innovation communication is applied in the implementation of Electronic Traffic Law Enforcement (ETLE) services to improve traffic discipline in Samarinda City. This involves various strategies such as campaigns on social media, counseling in schools and companies, distribution of brochures on the streets, and direct interaction between officers and road users..